Influences of Computer Network Technology on Army Equipment Informatization Construction. Issue 2 (March 2019) - Zhang, Tianpeng; Liu, Tielin; Gao, Jian; Li, Can; Xue, Hui
Abstract: Computer network technology has brought revolutionary changes to Modern Warfare. The computer network is the product of information age.In this paper, the concept of network technology and information equipment is introduced, and the role of network technology in promoting the army's information equipment construction is highlighted.